Bacterial Otitis Externa in Patients Attending an ENT Clinic in Babol, North of Iran - Kiakojuri, Keyvan (Jundishapur J Microbiol, 2016)
BACKGROUND: Acute otitis externa, an inflammatory condition of the external auditory canal, is a common clinical problem in general medicine. OBJECTIVES: This study aimed to determine the etiology of otitis externa in patients from the Mazandaran province, north of Iran, which has a humid climate, as humidity can affect the prevalence of pathogenic microorganisms. PATIENTS AND METHODS: This cross-sectional study involved 116 patients with otitis externa. Two sets of samples were collected from their ears; one set was used for slide preparations, and the other for microbial culturing. After culturing, the microorganisms were identified by conventional methods. RESULTS: Patients between 35 and 44 years of age were most frequently affected (25.00%) by otitis externa (average age, 43.87 ± 18.08 years). Moreover, women (54.31%) were more frequently affected than men (45.69%). Upon direct investigation, Gram-positive bacilli were the most commonly identified microorganisms (22.41%). Furthermore, Bacillus spp. and coagulase-negative staphylococci (22.41% and 19.83%, respectively), were the organisms most frequently identified from cultures of otitis externa samples. CONCLUSIONS: Direct examination and culture showed that a mixed infection of fungi and bacteria is the most common cause of otitis externa. The present study revealed that Bacilli spp. were the most abundant bacteria isolated from patients with otitis externa. Thus, it is recommended that both organisms should be considered as etiologic agents in protocols for treatment of otitis externa.